Poor self-reported health in association with sleep duration and health complaints among adolescents in Latvia - Klavina-Makrecka Solvita; Gobina Inese; Pudule Iveta; Velika Biruta; Grinberga Daiga; Villerusa Anita (SHS Web of Conferences, 2024)
Insufficient sleep and recurrent health complaints may increase the risk of poorer self-reported health in adolescence, yet the relationships between these factors are not well understood. This study aims to explore the association between poor self-reported health and insufficient sleep duration among 11, 13, and 15 years old adolescents in Latvia by assessing the moderation effects of age and gender and by considering the mediating effect of health complaints. Methods: Data from the Health Behaviour in School-aged Children Study on 2017/2018 of Latvia (n = 4412) were used for statistical analysis. Results: On average, 19.3% reported insufficient sleep duration on schooldays and 4.4% on non-school days. Of those with insufficient sleep duration, 5.8% reported poor self-reported health while this proportion was 2% among those with sufficient sleep. Poor self- reported health was associated insufficient sleep duration on school days (OR = 3.02; 95%CI 2.02-4.49), but not on non-schooldays. The association between insufficient sleep and poor self-reported health changed considerably after adjustment with health complaints (OR = 1.58;95%CI 1.03-2.43), however, it still remained significant. Conclusions: There is significant association between insufficient sleep and poor self-reported health regardless of total burden of health complaints.